Association between Body Composition and Dysphagia in Patients with Amyotrophic Lateral Sclerosis - Cristina Salvioni; Adriana Leico Oda; Marco Orsini; Michele Pauli; Luciana M. Frabasile; Percilia C. L. Alves; Rosana M. Borges; Helena N. M. Sierra; Gabriela Menegatti; Márcio Ottoboni Pinho; Acary Souza Bulle Oliveira (MDPI AG, 2021)
Background: The influence of changes in body composition on swallowing in patients with Amyotrophic Lateral Sclerosis (ALS) is unknown. Understanding the interrelation between body compartments and dysphagia may establish specific treatments related to both nutritional aspects as to myofunctional ones designed to delay swallowing loss. Aim: The aim of the study was to evaluate the relationship between body composition and dysphagia during the course of the disease. Methods: The protocol of this study included assessments carried out quarterly for one year and included: analysis of body composition by multi-frequency segmental bioimpedance, nutritional diagnosis, maximum strength test of the tongue and lips, analysis of swallowing using the Functional Oral Intake Score (FOIS) and Swallowing Rating Scale of the American Speech-Language-Hearing Association (ASHA), speech intelligibility and analysis of disease severity. To measure the degree of relationship between quantitative variables, Spearman's correlation was used. Results: Thirty-four patients were evaluated, 28 Spinal Group and 6 Bulbar Group. The results did not show any significant differences in the analysis of body composition between the groups. Positive associations were found between body compartments and swallowing analysis. The phase angle showed a strong correlation between the FOIS scales (r = 0.74, p < 0.01), ASHA (r = 0.77, p < 0.01) and tongue (r = 0.66, p < 0.01). Conclusions: Changes in body compartments were related to swallowing functionality and speech intelligibility in ALS patients, emphasizing the importance of analyzing body compartments for decision making by the interdisciplinary team. Although these preliminary data were collected in a small sample size, they serve to motivate future studies in this area.